2008
DOI: 10.1111/j.1742-7924.2008.00106.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of pressure ulcer and physical restraint prevalence in Japanese acute care units

Abstract: Aim: To investigate the predictors of pressure ulcer and physical restraint prevalence in Japanese acute care units and their relationship to the nursing hours, skill mix, and Nursing Need Scores (NNS). Methods: In this descriptive study, quantitative methods were employed to determine if pressure ulcers and physical restraint prevalence, as outcomes of nursing care, were related to the nursing hours, skill mix, and intensity of nursing-care needs. The sample included 87 acute care units in 42 hospitals in Tok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…Eight mostly weak studies gave no strong evidence of beneficial associations between nursing support worker staffing and patient safety. Studies found no association with mortality (Unruh et al, 2007), failure to rescue (Park et al, 2012), length of stay (Unruh et al, 2007), venous thromboembolism (Ibe et al, 2008), or missed care . However, higher assistant staffing was associated with higher rates of falls (Hart andDavis, 2011, Lake et al, 2010), pressure ulcers (Seago et al, 2006), readmission rates (Weiss et al, 2011), medication errors (Seago et al, 2006), use of physical restraints M a n u s c r i p t…”
Section: O U T C O M E S a S S O C I A T E D W I T H N U R S I N G A mentioning
confidence: 98%
See 2 more Smart Citations
“…Eight mostly weak studies gave no strong evidence of beneficial associations between nursing support worker staffing and patient safety. Studies found no association with mortality (Unruh et al, 2007), failure to rescue (Park et al, 2012), length of stay (Unruh et al, 2007), venous thromboembolism (Ibe et al, 2008), or missed care . However, higher assistant staffing was associated with higher rates of falls (Hart andDavis, 2011, Lake et al, 2010), pressure ulcers (Seago et al, 2006), readmission rates (Weiss et al, 2011), medication errors (Seago et al, 2006), use of physical restraints M a n u s c r i p t…”
Section: O U T C O M E S a S S O C I A T E D W I T H N U R S I N G A mentioning
confidence: 98%
“…Page 11 (Hart and Davis, 2011) and lower levels of patient satisfaction (Seago et al, 2006), although one weak study found that higher HCA staffing levels were associated with lower rates of pressure ulcers (Ibe et al, 2008). …”
Section: March 2016mentioning
confidence: 99%
See 1 more Smart Citation
“…Eight, mostly weak, studies gave no strong evidence of beneficial associations between nursing assistant staffing levels and patient safety. Studies found no association between assistant staffing level and mortality, 46 failure to rescue, 47 length of stay, 46 venous thromboembolism 48 or missed care. 19 However, higher assistant staffing was associated with higher rates of falls, 43,49 pressure ulcers, 50 readmission rates, 51 medication errors 50 and use of physical restraints 43 and lower levels of patient satisfaction.…”
Section: Skill MIX and Nursing Assistantsmentioning
confidence: 99%
“…Although prevention of PUs is a multidisciplinary responsibility, nurses play a major role. In a study on Japanese nurses, long work hours were found to increase the prevalence of physical restraint and PUs (20).…”
mentioning
confidence: 99%